Students’ Perceptions of Using Computer Based-Test (CBT) for Summative Assessment in Mata Kuliah Umum (MKU) Bahasa Inggris Course at Universitas Negeri Padang - Sausan, Nisrina Khansa; Oktoviandry, Rifki (Universitas Negeri Padang, 2024)
This research aims to review and explore students’ perceptions of the use of computer-based test (CBT) in the final examination of Mata Kuliah Umum (MKU) Bahasa Inggris at Universitas Negeri Padang. For this research, an online questionnaire comprising 15 statements which adapted from Sauti (2020) were utilized. Also, an interview with consisting of 5 questions were constructed by the researcher. The participants were 97 students from the different study programs and faculties at UNP. The findings from the data analysis show that most students positively perceive the use of CBT in their final exams. The positive was revealed by indicating its perceived usefulness, academic benefits, pleasantness, and efficiency compared to PBT methods. On the other side, there were some obstacles that students faced when using CBT that revealed by indicating the need for extra time of familiarity with operating devices, the internet connection, technical issues, potential health concerns, and the test schedules. The findings of this research are expected to serve as guidance for educators in appraising future assessments, as well as a source of reference for subsequent researchers conducting more advanced investigations.This research aims to review and explore students’ perceptions of the use of computer-based test (CBT) in the final examination of Mata Kuliah Umum (MKU) Bahasa Inggris at Universitas Negeri Padang. For this research, an online questionnaire comprising 15 statements which adapted from Sauti (2020)were utilized. Also, an interview with consisting of 5 questions were constructed by the researcher. The participants were 97 students from the different study programs and faculties at UNP. The findings from the data analysis show that most students positively perceive the use of CBT in their final exams. The positive was revealed by indicating its perceived usefulness, academic benefits, pleasantness, and efficiency compared to PBT methods. On the other side, there were some obstacles that students faced when using CBT that revealed by indicating the need for extra time of familiarity with operating devices, the internet connection, technical issues, potential health concerns, and the test schedules. The findings of this research are expected to serve as guidance for educators in appraising future assessments, as well as a source of reference for subsequent researchers conducting more advanced investigations.